دور مواد البناء في تحقيق استدامة الأبنية وفق أنظمة الاستدامة العالمية (حالة دراسية الأبنية الإدارية) - هاني ودح; رولا نتيفة; خديجة طنجور (Tishreen University, 2019)
The principles of environmental design became the basis of architectural thought from the early stages of the design process and the completion of the selection of suitable building materials for the achievement of sustainable buildings, and in light of the trends and challenges to achieve sustainability and sustainable development, especially in the field of architecture, architects and constructors began using everything new In the world of construction, in order to achieve sustainable architectural design, which led to a qualitative architectural shift led to the discovery of building materials and contribute to the achievement of sustainability strategies in terms of architecture and urban development. This study focused on the role of building materials and construction and their impact on the sustainability of administrative buildings. The development of construction materials in recent decades resulted in distinguished projects aimed at preserving the environment, energy and reducing pollution. The choice of local administrative buildings because they are considered expensive buildings in the operation and the implementation of sustainability strategies on such buildings in a way that contributes significantly to increase the productivity of employees and stimulate their potential by providing a comfortable working environment for them. In this research, we will attempt to find the mechanisms for selecting sustainable building materials through analyzing and comparing the standard of construction and construction in the most famous global environmental systems, and to identify the points that these systems participated in. This step aims to identify the most important criteria that assess the efficiency of building materials in administrative buildings and to take advantage of these standards in the process of selecting building materials in the pre-construction phase of future administrative buildings.   أصبحت مبادئ التصميم البيئي أساسا للفكر المعماري ابتداء من المراحل الأولى للعملية التصميمية وانتهاء باختيار المواد البنائية المناسبة من اجل تحقيق أبنية مستدامة، وفي ظل التوجهات والتحديات لتحقيق الاستدامة والتنمية المستدامة ولاسيما في مجال العمارة، بدأ المعماريون والانشائيون باستخدام كل ماهو جديد في عالم  البناء وذلك في سبيل التوصل إلى تصميم معماري مستدام، الأمر الذي أدى إلى نقلة  معمارية نوعية أدت إلى اكتشاف مواد بنائية وإنشائية  تساهم في تحقيق استراتيجيات الاستدامة على صعيد العمارة والتطور العمراني. لذا ركزت هذه الدراسة على دور مواد البناء والإنشاء وأثرها في تحقيق استدامة الأبنية الإدارية، حيث نتج عن التطور الذي شهدته مواد البناء في العقود الأخيرة مشاريع متميزة هدفها الحفاظ على البيئة والطاقة وتقليل التلوث.    تأتي أهمية هذه الدراسة من خلال تسليط الضوء على الأبنية الإدارية لأنها تعتبر من الأبنية المكلفة في التشغيل   كما أن تطبيق استراتيجيات الاستدامة على مثل هذا النوع من الأبنية بشكل كامل يساهم بشكل كبير في تخفيض استهلاك الطاقة وزيادة إنتاجية العاملين ويحفز إمكانياتهم وذلك بتأمين بيئة عمل مريحة لهم. ولقد توصلنا بنتيجة هذه الدراسة إلى تحديد أهم النقاط لاختيار مواد البناء المستدامة من خلال تحليل معيار مادة البناء والإنشاء ضمن أشهر الأنظمة البيئية العالمية ومقارنتها، وتحديد البنود التي اشتركت بها تلك الأنظمة، وقمنا باختبارها على مشاريع رائدة في مجال الاستدامة. وتهدف هذه الخطوة إلى تحديد أهم المعايير التي تقيم كفاءة مواد البناء في الأبنية الإدارية القائمة والاستفادة من هذه المعايير في عملية اختيار مواد البناء في مرحلة ماقبل الإنشاء للأبنية الإدارية المستقبلية.